Relationship between level of physical activity and body mass index among senior high school students - I Gede Panji Harta Danu; I Wayan Sugiritama; Ni Luh Nopi Andayani; Luh Putu Ratna Sundari (Universitas Udayana dan Diaspora Taipei Medical University, 2023)
Background: The development of the times causes technology to also experience development. As a result, many activities that previously required excess energy can now be easily done and also more practical. On the other hand, the development of this technology has a bad impact, where a person becomes less active in carrying out his daily activities, which can affect his lifestyle. Low physical activity can have an impact on body mass index that becomes not ideal. The purpose of this study was to analyze the relationship between physical activity level and body mass index in students of senior high school. Methods: This study used the cross-sectional design. The research was conducted offline or directly in the field. Results: The results of Spearman's rho correlation test showed a value of p= 0.000 (p< 0.05) and a correlation coefficient value of -0.502. Conclusion: There is a significant relationship between physical activity level and body mass index in students of senior high school with sufficient correlation strength. The value of the correlation coefficient shows negative results which indicate a unidirectional relationship between the two variables, where the lower the level of physical activity, the higher the value of a person's body mass index and vice versa.